A Comparative Study of Aqueous Polymerization of Acrylonitrile in Presence of Oxygen and Nitrogen Atmosphere - Shukla, J.S.; Dixit, S.K.; Shukla, S.K. (Asian Journal of Chemistry, 2010)
Heterogeneous polymerization of acrylonitrile (AN) initiated by potassium bromate-thiomalic acid (TMA) redox couple was studied in the atmosphere of oxygen and nitrogen in aqueous medium. The square root dependence of rate on initiator, activator and monomer concentration was observed. The activation energy and the number average molecular weight were higher in oxygen atmosphere.